The effect of educational mismatch on wages using European panel data - Irlondo, Inaki; Pérez-Amaral, Teodosio (London, 2013)
"This paper analyzes the effect of educational mismatch on wages, using a rich panel dataset of workers in the major euro area countries from 2006 to 2009, drawn from the European Union Statistics on Income and Living Conditions (Eurostat). We use a consistent estimator to address the two econometric problems faced by the empirical literature: the omitted variable bias and measurement error. In principle, our fixed effect estimates confirm that overeducated workers suffer a wage penalty of similar magnitude to the return on each year of schooling attained. Interestingly, when we split the sample by age, we find that the wages of people aged under 35 basically depend on the level of education attained, while those of workers aged over 35 depend on job educational requirements. These results are interpreted taking into account the impact of the depreciation of skills on human capital. The main policy implication of the paper is that overeducation constitutes a waste of resources. Therefore public authorities should seek to reduce the negative impact of overeducation on the labor market."